Inflammatory Mechanisms and Treatments of Alzheimer’s Disease: An Integrative Review of Neuroscience and Bioinformatics - Li, Bangyu (Transactions on Materials, Biotechnology and Life Sciences, 2024)
The most common type of dementia, Alzheimer’s disease (AD), is characterized by plaques of amyloid-beta (Aβ) and then tangles of tau protein aggregating in the brain, causing neurodegeneration and cognitive decline. The association between neuroinflammation and the pathogenesis of AD has come to be increasingly well acknowledged. This review discusses the inflammatory pathways involved in AD, focusing on microglia and astrocytes, as well as the involvement of various proinflammatory cytokines (i.e., TNF-α and IL-1β). The NF-κB signaling and the NLRP3 inflammasome are also reviewed for their effects on neuronal death and cognitive dysfunction. Additionally, the unifying function of bioinformatics in AD research, combining genomic and transcriptomic analyses with proteomics and metabolomics, is explored. These tools have uncovered crucial genetic and molecular pathways associated with inflammatory cross-talks in AD, revealing possible drug targets. An overview of treatments such as nonsteroidal anti-inflammatory drugs (NSAIDs), immunotherapies, and newer therapies like stem cell therapy and RNA interference is provided, along with their efficacy and drawbacks. The review concludes by highlighting the importance of multidisciplinary approaches and individualized therapies to enhance therapeutic outcomes in AD patients.